AB0319 Body mass index and disease activity parameters in patients with established rheumatoid arthritis. (23rd January 2014) - Bernardes, M.; Terroso, G.; Aleixo, A.; Madureira, P.; Vieira, R.; Bernardo, A.; Pimenta, S.; Martins, M.J.; Machado, J.C.; Simões-Ventura, F.
Abstract : Background: The definitive role of adipose tissue in rheumatoid arthritis (RA) is not established. Patients with RA and a high body mass index (BMI) have demonstrated significantly less radiographic joint damage than those with low BMI. 1 On the other hand, in another paper, increasing BMI was negatively correlated with clinical response to biologic therapy in active RA patients. 2 Objectives: To study the association of disease activity with BMI in patients with established RA, analyzing the differences according to therapy regimens (conventional DMARDs, exclusively, versus biologics, with or without conventional DMARDs). Methods: Clinical caracteristics, including BMI, and blood samples were collected in a monitoring visit. Portuguese version of the Standford Health Assessment Questionnaire (HAQ), Disease Activity Score four variables (DAS28 (4v)), 68 tender (TJC) and 66 swollen joint counts (SJC) were obtained. We measured ESR and CRP. PASW Statistics 18 was used for statistical analysis. Results: We evaluated 203 RA patients, 138 (68%) women, 103 (51%) under biologics, age 53±12 years, 14±10 years of disease duration, mean DAS28 (4v) of 4.26±1.32 and a mean HAQ of 1.250±0.680. Seventy two (36%) had a BMI<25 kg/m 2, 86 (42%) had a BMI of 25-<30 kg/m 2 and 45 (22%) had a BMI≥30 kg/m 2 . In a multivariate modelling (after adjusting for age, disease duration, average daily dose of prednisone and years of corticosteroid use) and in RA patients exclusively under conventional DMARDs, obesity was associated with lower SJC (p=0.005) and higher DAS28 (4v) (p<0.001), TJC (p<0.005) and HAQ (p<0.001) values. Using the same model and adjusting also for years of biologic therapy, in the group under biologic agents, overweight was associated with lower DAS28 (4v) (p<0.05), TJC (p=0.001) and HAQ (p=0.001) values. CRP and ESR were not significantly associated with BMI. Conclusions: In our RA population under conventional DMARDs, subjects with higher BMI exhibited higher disease activity parameters. Paradoxically, in the group under biologics, overweight showed a better disease control. These facts reinforce the need of other studies to clarify the different regulatory effects of adipose tissue on RA treatment responses according the therapy regimen. References: Westhoff G. et al. Arthritis Rheum 2007; 56: 3575-82 Klaasen R. et al. Arthritis Rheum 2011; 63. 359-64 Disclosure of Interest: None Declared